Trade and investment policies and regional economic integration in East Asia - Siow Yue Chia (Asian Development Bank Institute (ADBI), 2010)
The global economic crisis has affected the East Asian economies via trade and investment. The export-led model which had been responsible for the East Asian Miracle now must redirect the basis of growth from exports sent to the US and Europe to regional and domestic demand. Regional trade integration has been market-led through production networks and foreign direct investment (FDI). Since the proliferation of bilateral and plurilateral free trade agreements (FTA) and economic partnership agreements (EPA) has not resulted in an integrated regional market, it is important that East Asia seek an arrangement for a region-wide FTA/EPA. Currently, there are proposals for an ASEAN+3, an ASEAN+6, Pan-Asia, and Asia Pacific initiatives. While proponents of a region-wide FTA/EPA highlight its benefits, skeptics and critics point to the difficulties of reaching consensus in a region with widely varying political, economic, and social systems. Ultimately it will depend on a political-economic decision based on a cost-benefit analysis of liberalization, facilitation, and cooperation in a region-wide FTA.
Keywords: F13; F14; F26; O24; 330; Handelsregionalismus; Außenhandelsliberalisierung; Direktinvestition; Freihandelszone; Außenhandelseffekt; Makroökonomischer Einfluss; Ostasien